Accramycin A, A New Aromatic Polyketide, from the Soil Bacterium, Streptomyces sp. MA37 - Fleurdeliz Maglangit (Molecules, 2019)
Drug-like molecules are known to contain many different building blocks with great potential as pharmacophores for drug discovery. The continued search for unique scaffolds in our laboratory led to the isolation of a novel Ghanaian soil bacterium, Streptomyces sp. MA37. This strain produces many bioactive molecules, most of which belong to carbazoles, pyrrolizidines, and fluorinated metabolites. Further probing of the metabolites of MA37 has led to the discovery of a new naphthacene-type aromatic natural product, which we have named accramycin A 1. This molecule was isolated using an HPLC-photodiode array (PDA) guided isolation process and MS/MS molecular networking. The structure of 1 was characterized by detailed analysis of LC-MS, UV, 1D, and 2D NMR data. Preliminary studies on the antibacterial properties of 1 using Group B Streptococcus (GBS) produced a minimum inhibitory concentration (MIC) of 27 µg/mL. This represents the first report of such bioactivity amongst the naphthacene-type aromatic polyketides, and also suggests the possibility for the further development of potent molecules against GBS based on the accramycin scaffold. A putative acc biosynthetic pathway for accramycin, featuring a tridecaketide-specific type II polyketide synthase, was proposed.